Evaluating the impact of digital technologies on the excursion services’ management - Olesia Suntsova (Фінансово-кредитні системи: перспективи розвитку.)
This article explores the effectiveness of integrating innovative digital technologies in the organization and management of excursion services. The rapid advancement of digital tools, including augmented reality (AR), virtual reality (VR), artificial intelligence (AI), and mobile applications, has significantly transformed the tourism industry, creating new opportunities for enhancing customer experience, optimizing service delivery, and increasing business efficiency. Excursion activities, in particular, benefit from these developments by expanding their audience reach, improving interactivity, and offering personalized and immersive experiences.